Los dones de Uruapan: Salvador Martínez Aceves, Carlos Barragán Sánchez, Francisco Barragán Vivas. Campo de acción empresarial y desarrollo agroindustrial en la región de la Tierra Caliente y Uruapan, Michoacán. 1940-1970 - Yácuta García, Rosa Elena (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
The present investigation .cuyo fears power station it is the evolution and development of a representative group of the managerial activity of the city of Uruapan, Michoacán - it is located inside the field of the economic history, the one that, in turn, it frames the study of the managerial history, gender of early it dates in our country. This focus requires of the revision of the theories it has more than enough history and managerial theory developed by authors like Alfred Chandler and Douglass C. North, besides the delimitation of the elements that you/they define to a region, understanding for this the space in the one which the actors social interactúan in the exercise of its economic tasks and its relationships with the political and government groups with those who are related. "The empresariado (...) studied as a social fellow whose force politics derives of the economic power that accumulates."1 according to the theses exposed by Douglass C. North, the institutions are creation of the human societies and their objective is to offer stability in the interaction that is believed among their components. It is about bodies of norms that regulate the economic, social and political activities, establishing limits inside which is operated, that which is translated in offering mechanisms of security that guarantee, among other situations, the rights of property. The violation of these limits can be sanctioned by the established organisms for fungir like authority.

La presente investigación –cuyo tema central es la evolución y desarrollo de un grupo representativo de la actividad empresarial de la ciudad de Uruapan, Michoacán- se ubica dentro del campo de la historia económica, la que, a su vez, enmarca el estudio de la historia empresarial, género de temprana data en nuestro país. Este enfoque requiere de la revisión de las teorías sobre historia y teoría empresarial desarrollada por autores como Alfred Chandler y Douglass C. North, además de la delimitación de los elementos que definen a una región, entendiendo por ésta el espacio en el cual los actores sociales interactúan en el ejercicio de sus tareas económicas y sus relaciones con los grupos políticos y gubernamentales con quienes se relacionan. “El empresariado (...) estudiado como un sujeto social, cuya fuerza política deriva del poder económico que acumula”.1 De acuerdo a las tesis expuestas por Douglass C. North, las instituciones son creación de las sociedades humanas y su objetivo es brindar estabilidad en la interacción que se crea entre sus componentes. Se trata de cuerpos de normas que reglamentan las actividades económicas, sociales y políticas, estableciendo límites dentro de los cuales se opera, lo cual se traduce en brindar mecanismos de seguridad que garanticen, entre otras situaciones, los derechos de propiedad. La violación de estos límites puede ser sancionada por los organismos establecidos para fungir como autoridad.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2010-0001; Opción en historia de México; Acción empresarial; Desarrollo agroindustrial; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2390